O circuito inferior da economia na principal área comercial de Campina Grande – PB: a permanência e expansão dos ambulantes e camelôs - Silva, Hosana Vieira da (2020)
This study is an analysis about the lower circuit of the urban economy facing the process of permanence and expansion experienced by street vendors, in the main commercial area of the Campina Grande city - PB, which operate in Calçadão, Praças das Bandeira and Clementino Procópio, as well as the Shopping Edson Diniz and Arcas Titão and Catedral. Thus, it is highlighted the experienced period between 2000 and 2018, temporal cut-out in which the central lower circuit of the city underwent significant transformations with the construction of the first “camelódromo” of the city, the conformation of two commercial areas eminently directed to the realization of the socioeconomic practices developed by street vendors, in addition to the increasing (re) appropriation of some of the Center's public spaces by these small traders. Given this discussion, the reflections forwarded throughout the study are based on the theory of two circuits of urban economy, elaborated by Milton Santos (1979), where the lower circuit is emphasized, since this subsystem is understood as an representation’s instance of the activities and services performed by economic agents/actors with reduced capital (Silveira, 2015). Concerning the methodological procedures, surveys, bibliographic reviews, photographic records, the use of questionnaires and the consummation of informal conversations were performed. Therefore, the analysis of the data obtained allowed us to state that the concentration of the commercial forms studied in the Campina Grande’s center is due to multiple factors, such as the flow of people who permeate the said spatial cut, the relative cheapening of the rents of the boxes, or the absence of this type of cost, in addition to other aspects that were revealing the totality of a global market